Prospects for the Development of Corporate Governance of Commercial Banks in the Conditions of the Digital Economy - Rakhimov Jasur To’lqin o’g’li (Research Parks Publishing LLC, 2021)
this article discusses the necessary organizational structure to identify and control over the achievement of strategic objectives of commercial banks in corporate governance activities in the conditions of the digital economy, as well as a set of relations between banking management bodies and other interested parties, including the creation of competence and responsibility of corporate governance bodies in the conditions of the